ANALISIS MANFAAT BIAYA BIOCHAR DI LAHAN PERTANIAN UNTUK MENINGKATKAN PENDAPATAN PETANI DI KABUPATEN MERAUKE - Maria Magdalena Diana Widiastuti (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2016)
Biochar has been proven to increase the availability of  soil nutrient, yield productivity and farmers income. Biochar can be made from forestry/agricultural waste and do not required high technology. The objective of  this study were: (1) to analyze Benefit Cost Ratio (BCR) of  biochar made from rice husk, (2) to compare yield productivity of  paddy with biochar treatment, and (3) to analyze of  paddy farming system with biochar treatment. The methodology by using BCR and productivity approach. The result showed that, firstly, the BCR of  biochar from rice husks was 1.35 which indicated that biochar productivity  as feasible. Secondly, the provision of  biochar and fertilizer on agricultural could increase rice productivity of  4.2 ton/ha (control treatment) to 5.5 ton/ha (treatment biochar + organic fertilizer) and 6 ton/ha (treatment biochar + organic fertilizer + chemical fertilizers). Thirdly, the benefit cost ratio of  paddy farming system for control treatment (1.54), higher than biochar+organic fertilizer treatment (1.46) and biochar+organic fertilizer+chemical fertilizer treatment.